2011
DOI: 10.1111/j.1365-2710.2011.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of ITPA 94C>A and risk of adverse effects among patients with acute lymphoblastic leukaemia treated with 6-mercaptopurine

Abstract: Our results suggest that ITPA 94C>A testing, but not TPMT testing, may help in minimizing the adverse effects of 6-MP in Malaysian patients. However, whether this is true in clinical practice requires a larger study and formal randomized controlled evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 15 publications
(33 reference statements)
1
35
0
Order By: Relevance
“…In a study of 62 IBD patients, positive association was observed between ITPA C94A and increased adverse events other than leucopenia [35]. In ALL patients, this variant was associated with the pyrexia and hepatotoxicity [36] and severe febrile neutropenia, indicating the clinical relevance of this variant in 6-MP dose adjustment [37]. In the current study, we also investigated the association of ITPA 94 C→ A with myelotoxicity, which is consistent with Marinaki et al who showed association with leucopenia and a high frequency of febrile episodes [35].…”
Section: Discussionmentioning
confidence: 97%
“…In a study of 62 IBD patients, positive association was observed between ITPA C94A and increased adverse events other than leucopenia [35]. In ALL patients, this variant was associated with the pyrexia and hepatotoxicity [36] and severe febrile neutropenia, indicating the clinical relevance of this variant in 6-MP dose adjustment [37]. In the current study, we also investigated the association of ITPA 94 C→ A with myelotoxicity, which is consistent with Marinaki et al who showed association with leucopenia and a high frequency of febrile episodes [35].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Guatemalan admixed populations have one of the highest observed toxicity risk rates for treatments based on thiopurine drugs (17 %, see Table 1). This percentage could be an underestimate, considering that at least 20 additional mutant variants have been identified in TPMT (TPMT*3D, *4, *5, *6, *7, *8, *10, *23, *28, etc) and that SNPs in other genes, such as inosine triphosphate pyrophosphohydrolase (ITPA 94C>A) also affect thiopurine metabolism (3, 15, 29, 50). …”
Section: Discussionmentioning
confidence: 99%
“…The ITPA variant allele (rs1127354) is associated with nonfunctionality of the enzyme and is found with an allelic frequency ranging from 5 to 19%, with the lower end of the range seen in Caucasian populations and the higher range seen in Asian populations [96]. The polymorphism is associated with higher concentrations of methylated nucleotide metabolites of 6-MP in cells, as well as higher incidence of severe hepatotoxicity, even after adjustment for TPMT genotype [62][63][64][65][66]. Furthermore, a variant in the PACSIN2 gene has been found to modulate the activity of TPMT and is also independently associated with severe gastrointestinal toxicity due to 6-MP [70].…”
Section: Gastrointestinal Toxicitymentioning
confidence: 97%